Stable Isotope Data from Diets and Tissues of Captive Bears Fed Experimental Diets ... - Karyn D Rode (U.S. Geological Survey, 2016)
This dataset contains stable isotope incorporation and discrimination results for several sets of feeding experiments with captive brown and polar bears. Experiments were designed to determine the effects of dietary lipid content and fasting behavior on discrimination in blood, hair, and fat. Data are divided into three components of the study: one to estimate isotopic discrimination with varying dietary lipid content, one to estimate the potential effects of fasting on tissue isotope values, and one to determine incorporation rates of isotopes in various tissues. The experiments were conducted between 2009 and 2013 with captive grizzly bears at Washington State University and captive polar bears at the Oregon and Alaska zoos. ...